Is apparent digestibility associated with residual feed intake and enteric methane emission in Nellore cattle? - Gianvecchio, Sarah Bernardes [UNESP]; Sakamoto, Leandro Sannomiya [UNESP]; Souza, Luana Lelis [UNESP]; Benfica, Lorena Ferreira [UNESP]; Marcatto, Juliana de Oliveira Santos; Paula, Eduardo Marostegan de; Malheiros, Jessica Moraes; Canesin, Roberta Carrilho; Bonilha, Sarah Figueiredo Martins; Albuquerque, Lucia Galvao de [UNESP]; Mercadante, Maria Eugenia Zerlotti [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2024)
This study was conducted to evaluate the relationship among digestibility, residual feed intake (RFI), and enteric methane emission in growing Nellore cattle ( Bos indicus) divergently classified based on RFI phenotype and breeding value (EBVRFI). Animals (n = 122) subjected to performance testing (forage:concentrate ratio of 60:40) in two test groups were classified based on RFI. A sample of 80 animals classified as low (-0.748 +/- 0.076 kg DM/day) or high (0.775 +/- 0.075 kg DM/day) RFI was evaluated regarding feed compounds digestibility, fecal excretion, and methane emission (CH4, g/day). Statistical mixed models included fixed effects of RFI (or EBVRFI), linear effect of initial age as covariate, and the random effects of the test group. There was no difference in the digestibility of feed compounds between the most and least efficient animals. However, dry matter intake (DMI; 6.92 vs. 8.66 kg DM/day) and feed conversion (7.93 vs. 9.42 kg/kg) were lesser in low RFI animals. On average, low RFI animals emitted 14.3 g less CH4 per day (174 vs. 188 g CH4/day); however, CH4 emission expressed as g/kg DMI (23.1 vs. 20.1) and the percentage of gross energy intake lost as CH4 (8.13 vs. 7.08%) were greater for these animals. These results showed the benefits of using more feed efficient animals in the beef production chain, i.e., animals that exhibit lower feed intake, lower fecal excretion, and lower enteric methane emission without differences in weight gain or body weight. However, the variations in feed efficiency among them cannot be explained by differences in dry matter or feed compounds digestibility. More efficient animals emit less enteric methane than less efficient animals, probably as a result of lower DMI.
Keywords: beef cattle; digestion; feed efficiency; greenhouse gases emissions